Doing adaptive management at Sida (Tim Ruffer, 2019)
Lessons from the market systems development approach The evaluation focuses on Sida’s management of MSD projects. The projects are applying the MSD approach with an aim to: - contribute to improved MSD programming by Sida through better management practices across the project cycle - generate recommendations on how Sida can create conducive conditions for systems approaches and adaptive programming more generally. The brief assesses Sida’s organisational capacity for adaptive management in three dimensions: - leadership and culture - staff capacities - skills, and systems and procedures